Implementation of an Augmented Reality-Based Mystery Box Reward Media to Enhance Students' Self-Efficacy in Islamic Religious Education Learning - Wiwik Idayati; Moh. Mundzir (Al-Fikru: Jurnal Ilmiah, 2026)
Low self-efficacy among students in Islamic Religious Education  is a major issue in Class X-E at SMAN 3 Tuban. This situation is characterized by low active participation, hesitation in answering questions, and a lack of confidence in one’s own abilities. This study aims to describe the implementation of the Augmented Reality (AR)-based “Mystery Box Reward” media and analyze its impact on improving students' self-efficacy. The study employed a Classroom Action Research (CAR) design conducted in two cycles, each comprising planning, action, observation, and reflection stages. Data were collected through self-efficacy questionnaires, observations, interviews, and documentation. The research subjects consisted of 32 students who participated in the entire series of research activities. The results showed a significant increase in self-efficacy, from 65.47% in the pre-cycle to 77.94% in Cycle I and 88.75% in Cycle II. Classical mastery increased from 15.62% to 68.75% and reached 96.88% at the end of Cycle II. Observation data also showed an increase in active participation from 57.94% to 95.83%. These findings indicate that the AR-based Mystery Box Reward medium is effective in enhancing self-efficacy through positive reinforcement, engaging learning experiences, and higher student engagement.